PKM Pelatihan Dan Workshop Pembuatan Briket Arang Dan Asap Cair Pada Perkebunan Kakao Di Desa Budi Mukti Kecamatan Damsol - Hamzah, Baharuddin; Rahmawati, Sitti (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2018)
This Community Partnership Program involved partners of farmer group in Budimukti Village, Damsol District,Donggala Regency, namely Panca Jaya and Subur Jaya farmer groups. Problems faced by both partners were: a) Cocoa shellsaround the cocoa plantations were increasingly piling up and left without handling because there was no technology toprocess the waste to have economic value to improve community?s standard of living. b) The surrounding community did notknow that cocoa shells can be processed to be charcoal briquettes as an alternative fuel to replace kerosene and to be liquidsmoke as a natural insecticide and preservative. c) They did not have skills in making charcoal briquettes and liquid smokefrom cocoa waste as raw material. The program aimed at improving farmers' knowledge and skills in designing technology tomake charcoal briquettes from cocoa shell waste and techniques in making liquid smoke from cocoa shell waste and theirrespective uses. The methods used were counseling and training as well as the practice of designing technology to makecharcoal briquettes and assembling technology for making liquid smoke from cocoa shell waste. Assistance to members ofpartnership groups was carried out with Participatory Methods. Extension activities were carried out in an effort to improvetheir knowledge, while training and demonstration plots were carried out in an effort to accelerate the process of technologytransfer to the community. The end results of this program were the increase in farmers? knowledge and the availability oftechnology packages for making charcoal briquettes and making liquid smoke from cocoa shell waste, so that the targetgroups can be independent in carrying out business activities using cocoa shell waste using the technology that had beenpracticed, on an ongoing basis